Cardiovascular Benefits of Omega-3 Polyunsaturated Fatty Acids - Maisch, Bernhard (IOS Press, 2013)
Focuses on the effect of [OMEGA]-3 polyunsaturated fatty acids on different risk factors in patients with cardiovascular disease. This work also considers aspects of prevention of cardiovascular disease, risk factors and pharmacokinetics of [OMEGA]-3 fatty acids ethyl esters